Pendampingan Implementasi Model Pembelajaran OIDDE untuk Meningkatkan Keterampilan Pembelajaran Berorientasi Etika di MA Muhammadiyah 1 Plus Malang - Hudha, Atok Miftachul; Husamah, H. (Universitas Pendidikan Ganesha, 2019)
Ethical behavior does not necessarily arise, so that a process of forming ethical attitudes is needed for students, and one of them is through education (which requires the active role of the teacher, in the form of ethical oriented learning). This article aims to describe the implementation of mentoring activities for the implementation of the OIDDE learning model at MA Muhammadiyah 1 Plus Malang. The subject of this service was 21 teachers of the MA Muhammadiyah I Plus Malang. Service activities are held for 3 months. Implementation methods, namely discussions, interactive lectures, practices, and modeling. Service evaluation is carried out on aspects of the process. The results of the process evaluation showed that service was carried out according to plan, 100% of teachers were enthusiastic (seriously following all training sessions to completion), 90% actively asked, and there were representatives appointed by the madrasa to become model teachers.